Engineering design graphics : sketching, modeling, and visualization - Leake, James M.; Borgerson, Jacob L. (John Wiley & Sons, 2013)
James Leake's 2 nd Edition of Engineering Design Graphics builds upon the previous text with more in-depth and enhanced information on projection theory that provides instructional framework and freehand sketching for learning important graphical concepts